2021
DOI: 10.1155/2021/3225439
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Renin‐Angiotensin System (tRAS) Induce Intervertebral Disc Degeneration by Activating Oxidative Stress and Inflammatory Reaction

Abstract: Lumbar intervertebral disc degeneration (IDD) has been the major contributor to low back pain (LBP). IDD is an chronic inflammation process, with the activation of plentiful inflammation-related cytokines and ECM degradation-related enzymes. In the past few years, hypertension has been reported to correlate with LBP. In addition, the local tissue renin-angiotensin system (tRAS) has been identified in multiple tissues, including the spinal cord, skin, kidney, heart, and bone. Recently, tRAS has also been establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 52 publications
(89 reference statements)
5
35
0
1
Order By: Relevance
“…These two methods have been depicted in detail in our previous study [ 28 ]. The primer sequences are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two methods have been depicted in detail in our previous study [ 28 ]. The primer sequences are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…These two methods have been explained in detail in our previous study [ 28 ]. The primary antibodies included CGRP (ab283568, 1 : 1000, Abcam, USA), CALCRL, RAMP1, type II collagen, Cleaved-caspase-3, iNOS, aggrecan, MMP3, and NF- κ B p65.…”
Section: Methodsmentioning
confidence: 99%
“…Previous evidence has shown that superoxide-triggered cell death is related to ferroptosis and OS and ECM degradation are involved in the pathogenesis of IDD [ 29 31 ]. Here, we were interested in whether ferroptosis participated in the NPC death and ECM degradation observed in IDD.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation was that the average age of the high-score group was greater than that of the other group, and age was an obvious risk factor of both IDD and hypertension. And there have been several studies on the effect of hypertension on IDD [ 31 , 32 ]. For example, Sun et al [ 31 ] found that the tissue renin-angiotensin system, a potential mechanism of developing hypertension, might contribute to IDD by oxidative stress and inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…And there have been several studies on the effect of hypertension on IDD [ 31 , 32 ]. For example, Sun et al [ 31 ] found that the tissue renin-angiotensin system, a potential mechanism of developing hypertension, might contribute to IDD by oxidative stress and inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%